Making of Donald Trump - Johnston, David Cay (London Melville House, 2016)
Love him or hate him, Trump's influence is undeniable. A man of great media savvy, entrepreneurial spirit, and political clout, Trump's career has been plagued by legal troubles and mounting controversy. Johnston tells the full story of how a boy from a quiet section of Queens, NY would become an entirely new, and complex, breed of public figure. Drawing on decades of interviews, financial records, court documents, and public statements, Johnston gives us the most in-depth look yet at the man who would be president.
Family history -- Family values -- Personal values -- A sickly child -- Making friends -- Trump's most important deals -- "A great lawsuit" -- Showing mercy -- Polish brigade -- Feelings and net worth -- Government rescues Trump -- Golf and taxes -- Income taxes -- Empty boxes -- "Better than Harvard" -- Trump charities -- Imaginary friends -- Imaginary lovers -- Myth maintenance -- Collecting honors -- Who's that? -- Down Mexico way -- Trump beaches a whale -- Biggest loser -- Epilogue.
Includes bibliographical references (pages 215-258) and index.
Keywords: Trump, Donald; Businessmen -- United States -- Biography; Real estate developers -- United States -- Biography; Celebrities -- United States -- Biography; Television personalities -- United States -- Biography; Presidential candidates -- United States -- Biography; Political campaigns -- United States -- History -- 21st century